À propos des Relatives Appositives. Syntaxe, sémantique, pragmatique - Jean-Charles Khalifa (Anglophonia)
Our purpose in this paper is to discuss the specificities, if any, of non-restrictive relative clauses (NRRCs). After a review of the two models that have been proposed to account for the syntax of NRRCs, namely the single constituent hypothesis and the main clause hypothesis, we go on to present the most significant results of a corpus study of those clauses. On the basis of a representative sample of 500, we try to lay the groundwork of a typology of NRRCs, showing in particular that the relative frequency of each of the 4 types we distinguish falls perfectly in line with the “perceptual hierarchy” proposed by psycholinguistics, not only for NRRCs, but for restrictive clauses as well, and which reflects syntactic complexity. We then conclude on pragmatic values of NRRCs in discourse.